2001
DOI: 10.4049/jimmunol.167.3.1566
|View full text |Cite
|
Sign up to set email alerts
|

Virally Infected Hepatocytes Are Resistant to Perforin-Dependent CTL Effector Mechanisms

Abstract: Cell-mediated cytotoxicity plays an important role in the clearance of noncytopathic viruses from infected tissues. Perforin-dependent cytotoxic mechanisms have been noted to play an important role in the clearance of infections from multiple extrahepatic organs. In contrast, mice with defects in the Fas/Fas ligand (FasL)-mediated cytotoxicity pathway exhibit delayed clearance of adenovirus from the liver without apparent delay in the clearance of viral infections from extrahepatic organs. The present studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 50 publications
6
66
0
1
Order By: Relevance
“…It might be in line with findings of Kafrouni et al [16]. These authors reported that virally infected hepatocytes become resistant to cytotoxic effector cells.…”
Section: Discussionsupporting
confidence: 81%
“…It might be in line with findings of Kafrouni et al [16]. These authors reported that virally infected hepatocytes become resistant to cytotoxic effector cells.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to deathligand induced apoptosis, granzyme B-mediated apoptosis largely depends on caspase activation and the sensitivity of the target cell. Hepatocytes seem resistant to granzyme B mediated cell death, and CTL killing of infected hepatocytes is perforin/granzyme B-independent [29,64] . Therefore, a contribution of this apoptosis mechanism in patients with viral hepatitis is very unlikely.…”
Section: Ligand-induced Hepatocyte Apoptosis In Hcv Infectionmentioning
confidence: 99%
“…In contrast, marked delay in hepatic adenoviral infection is noted in mice deficient in Fas, FasL, or TNF expression. 13,20,[23][24][25] However, mice with isolated defects in expression of TNFR1, the major mediator of TNF-induced apoptosis, clear hepatic adenoviral infection at rates similar to those in wild-type mice, whereas mice with defects in either TNF or tumor necrosis factor receptor 2 expression exhibit delays in adenoviral clearance that seem to be related to diminished activation of intrahepatic FasL-expressing CTL. 24 Thus, results of prior studies suggest that among the various CTL effector pathways, FasL/Fas-mediated cytotoxic effector mechanisms play the most prominent role in clearance of hepatic viral infections, 20,24 whereas the potential role of other cytotoxic effector mechanisms remains unclear.…”
mentioning
confidence: 99%
“…19 Despite the prominent role that the perforin-and granzyme-mediated granule exocytosis pathway plays in the clearance of a variety of extrahepatic viral infections, mice with isolated perforin deficiency do not exhibit deficiency in clearance of hepatic adenoviral infection. 20 Moreover, despite readily apparent delays in clearance of murine cytomegalovirus from the spleen 21 and salivary gland 22 of perforin-deficient mice, there is no delay in clearance of murine cytomegalovirus from the liver 21 of these mice. In contrast, marked delay in hepatic adenoviral infection is noted in mice deficient in Fas, FasL, or TNF expression.…”
mentioning
confidence: 99%